2002
DOI: 10.1007/bf03170524
|View full text |Cite
|
Sign up to set email alerts
|

On the simulation of inhomogeneous ESR lineshape of a spin probe in a liquid crystalline polymer

Abstract: A procedure for the analysis of the electron spin resonance (ESR) lineshape of a cholestane paramagnetic tracer dissolved in a liquid crystalline polymer is described. Due to its rodlike geometry, the cholestane probe is subjected to an anisotropic reorientational motion in the polymer matrix. On the basis of the generalized MorŸ theory, sirnulation approaches to the lineshape have been developed. The ESR lineshape has been calculated fora molecule reorienting in a homogeneous molecular site according to diffu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 31 publications
2
5
0
Order By: Relevance
“…Careful simulations proved that the inhomogeneous character of the ESR lineshapes was well taken into account by a two d-like distribution function of the molecular tracer sites, in agreement with previous results [14].…”
Section: Resultssupporting
confidence: 83%
“…Careful simulations proved that the inhomogeneous character of the ESR lineshapes was well taken into account by a two d-like distribution function of the molecular tracer sites, in agreement with previous results [14].…”
Section: Resultssupporting
confidence: 83%
“…7,51 In particular, a two δ-like distribution function, with a fast and a slow dynamic components, was shown to provide the best simulation of the ESR spectra. 51…”
Section: /36mentioning
confidence: 99%
“…In fact, a two‐ δ distribution function of the correlation times with fast and slow reorienting sites was shown to reproduce the experimental line‐shape better than log‐Gauss and square distributions. Moreover, we proved that assuming a bimodal log‐Gauss distribution did not improve the result obtained with the two‐ δ distribution 16…”
Section: Resultsmentioning
confidence: 81%
“…Many efforts were made to carefully take account of the inhomogeneous nature of the experimental line‐shape. The details of the study are reported elsewhere 16. The analysis led us to recognize the bimodal character of the distribution function of the spin‐probe sites.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation